Stylistic features of idioms and their cultural significance (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the stylistic features of idioms, emphasizing their importance in language expression and intercultural communication. Idioms, as stable expressions whose meanings go beyond their literal sense, significantly enrich language. The study examines the metaphorical nature, emotional coloring, and cultural background of idiomatic expressions. It also discusses how idioms enhance expressiveness and serve various communicative functions in discourse. Through illustrative examples, the article highlights the vivid imagery and concise conveyance of complex ideas that idioms provide. Ultimately, the analysis demonstrates that understanding idioms is essential for language proficiency and cultural awareness, revealing how idiomatic expressions reflect and shape human experience in diverse contexts.